Hsp31: a general stress protein of Escherichia coli - Baneyx, Francois (Henry Stewart Talks, 2007)
Stress proteins and molecular chaperones in E. coli, Hsp31: an ATP-regulated molecular chaperone, Hsp31 structure, Hsp31 mechanism of action, Role in the management of severe thermal stress, Regulation and mechanism of thermal induction, Induction by other stressors, Role in the management of acid stress
Archived at 2021/02/25